Search for photons above 10^18 eV with the hybrid detector of the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Samarai, I. Al; Albuquerque, I. F. M.; Allekotte, Ingomar; Almela, Daniel Alejandro; Castillo Alvarez, J.; Alvarez Muñiz, J.; Anastasi, G. A.; Anchordoqui, L.; Andrada, B.; et al. (IOP Publishing, 2017)
Fil: Aab, A.. Pierre Auger Observatory; Argentina